106 Senescence as a therapeutic target for myocardial ageing. (June 2018) - Walaszczyk, Anna; Dookun, Emily; Redgrave, Rachael; Tual-Chalot, Simon; Anderson, Rhys; Spyridopoulos, Ioakim; Owens, Andrew; Arthur, Helen; Richardson, Gavin; Passos, Joao
Abstract : Ageing is the biggest risk factor for impaired cardiovascular health, cardiovascular disease being the leading cause of death in 40% of individuals over 65 years old. Ageing is associated not only with an increased prevalence of cardiovascular disease but also with a poorer prognosis, including increased mortality or incidence of heart failure after myocardial infarction (MI). We have demonstrated that aged (23 month old) mice have an accumulation of cardiomyocyte senescence, reduced regenerative potential and display increased mortality as well as impaired recovery following MI. Cellular senescence is defined not only by the irreversible loss of division potential but also by the production of a senescence-associated secretory phenotype (SASP). This cocktail of pro-inflammatory cytokines, chemokines, matrix proteases and growth factors can impact on tissue function, inducing fibrosis, extracellular matrix degeneration and driving inflammation. We have therefore begun to test if clearance of senescent cardiomyocytes, using the senolytic compound Navitoclax, has the potential to improve cardiac health and post MI outcomes in aged animals. Following treatment with Navitoclax, but prior to MI, aged mice demonstrated a reduction in senescent cardiomyocytes which was associated increased cardiomyocyte generation, a decline in myocardial hypertrophy and a decrease in fibrosis. Following MI, Navitoclax treated mice displayed a tendency towards improved survival and had a significant improvement in cardiac function when compared to vehicle controls. We conclude that clearance of senescent cells is a potential therapeutic strategy for the treatment of age related cardiac dysfunction.